2013
DOI: 10.1086/674339
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Remodeling in Chronic Obstructive Pulmonary Disease is Lobe Dependent

Abstract: Pulmonary arterial remodeling has been demonstrated in patients with severe chronic obstructive pulmonary disease (COPD), but it is not known whether lobar heterogeneity of remodeling occurs. Furthermore, the relationship between pulmonary hypertension (PH) and pulmonary arterial remodeling in COPD has not been established. Muscular pulmonary arterial remodeling in arteries 0.10-0.25 mm in diameter was assessed in COPD-explanted lungs and autopsy controls. Remodeling was quantified as the percentage wall thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…This could be explained by the fact that the basal parenchymal and vascular remodeling may induce an apical vascular redistribution, thus increasing the number of vessels of large caliber. However, these results are in contradiction to the findings of Wrobel et al who evaluated the vascular remodeling on anatomical specimens of [0.10 -0.25] mm arteries of severe COPDs in terms of ratio of wall thickness to vessel diameter (WT%), and showed a larger WT% in the upper lung lobes [9]. This could be explained by the fact that the patients recruited in our study had severe emphysema predominating in the lower part of the lungs, which is unusual in COPD.…”
Section: Resultscontrasting
confidence: 85%
“…This could be explained by the fact that the basal parenchymal and vascular remodeling may induce an apical vascular redistribution, thus increasing the number of vessels of large caliber. However, these results are in contradiction to the findings of Wrobel et al who evaluated the vascular remodeling on anatomical specimens of [0.10 -0.25] mm arteries of severe COPDs in terms of ratio of wall thickness to vessel diameter (WT%), and showed a larger WT% in the upper lung lobes [9]. This could be explained by the fact that the patients recruited in our study had severe emphysema predominating in the lower part of the lungs, which is unusual in COPD.…”
Section: Resultscontrasting
confidence: 85%
“…In PH secondary to COPD, ongoing chronic hypoxic pulmonary vasoconstriction leads to changes that produce fixed remodeling of the pulmonary vasculature, namely fibromuscular intimal thickening and an increase in smooth muscle of the media of the pulmonary arterioles and arteries [7]. These same changes have also been noted in the pulmonary vasculature of smokers even without the presence of airflow obstruction [8].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Those vessel alterations are multiples and can happen at initial stage of COPD71 with endothelial dysfunction, inflammation, suggesting that the history of PH in COPD might be related with cigarette-smoke-induced endothelial alterations 73,74. The quantitative amount of emphysema in COPD was often negatively correlated to pulmonary microvasculature abnormalities measured using CT,7579 except for Wrobel et al,72 which did not find any significant correlation.…”
Section: Copd a Multi-compartment Diseasementioning
confidence: 95%
“…It has been shown that the toxicity of tobacco smoke affects bronchi and parenchyma, but can also directly alter pulmonary vessels both in animals70 and humans 6,71. At histological level, pulmonary arterial remodeling appeared to be more important in COPD than in control subjects, and is particularly important in upper lobe and in small muscular pulmonary arteries 72. Those vessel alterations are multiples and can happen at initial stage of COPD71 with endothelial dysfunction, inflammation, suggesting that the history of PH in COPD might be related with cigarette-smoke-induced endothelial alterations 73,74.…”
Section: Copd a Multi-compartment Diseasementioning
confidence: 99%